Calcul

-10+4²=
(-3²) -5x3+4=
(-200-70) /(-30)=
-3+4x8=
7+6x(-2)=
-60/4=
(-2)x(-5)x(+1)x(-6)=
(-2)-(-5)-(+1)+(-6)=

1
-10+4²=-10+16=6
(-3²) -5x3+4=9-15+4=-2
(-200-70) /(-30)=-270/(-30)=9
-3+4x8==-3+32= -29
7+6x(-2)=7+(-12)=7-12=-5
-60/4=-15
(-2)x(-5)x(+1)x(-6)=10*(-6)=-60
(-2)-(-5)-(+1)+(-6)=-2+7-1-6=-2

Réponses

2013-10-20T18:41:26+02:00
-10+4²=-10+16=6
(-3²) -5x3+4=9-15+4=-2
(-200-70) /(-30)=-270/(-30)=9
-3+4x8==-3+32= 29
7+6x(-2)=7+(-12)=7-12=-5
-60/4=-15
(-2)x(-5)x(+1)x(-6)=10*(-6)=-60
(-2)-(-5)-(+1)+(-6)=-2+5-1-6=-4